Small fatigue cracks : mechanics, mechanisms, and applications : proceedings of the Third Engineering Foundation International Conference, Turtle Bay Hilton, Oahu, Hawaii, December 6-11, 1998 /: mechanics, mechanisms, and applications : proceedings of the Third Engineering Foundation International Conference, Turtle Bay Hilton, Oahu, Hawaii, December 6-11, 1998. (1999) - Unknown
No abstract available